AMELIORATIVE EFFECTS OF NIGELLA SATIVA (KALVANJI) SEEDS ON SPERMATOGENESIS IN MICE WITH CISPLATIN-INDUCED TESTICULAR TOXICITY (The Research of Medical Science Review, 2025)
Background: Cisplatin-based chemotherapy is indicated for a variety of cancers such as tumors of testes, ovaries, lungs, urinary bladder, and lymphomas. However, its usefulness is marred by the adverse effect of the drug on spermatogenesis. Nowadays, herbs with claims of medicinal properties are being scientifically tested as a possible solution to drug-induced testicular injuries. Nigella sativa, commonly known as black cumin or kalvanji, is one such herb under investigation. Objectives: To determine the Ameliorative effects of Nigella sativa (Kalvanji) seeds on spermatogenesis in mice with Cisplatin-induced testicular toxicity Methodology: The study was conducted at the Institute of Basic Medical Sciences, Khyber Medical University, Peshawar and Department of Histopathology, Rehman Medical Institute, Peshawar. Twenty-eight male Swiss albino mice were included in this study. They were randomized into four study groups i.e. Control, Cisplatin, Nigella Seeds and Cisplatin + Nigella Seeds groups. Control and Nigella Seeds groups had four mice each while Cisplatin and Cisplatin + Nigella Seeds groups had ten mice each. The mice were sacrificed on the 6th day and body weight was measured. The testes were dissected out and gross morphological features including weight, shape, color and texture of the testes were noted. This was followed by preparation of testicular tissue slides stained with Eosin & Hematoxylin. Histological examination was carried out under light microscope. Extent of spermatogenesis was recorded in terms of Johnsen Score whereby a number between 1 and 10 is assigned to testicular tissue depending on the generations of spermatogenic cells observed - 1 indicating no evidence of spermatogenic cells and 10 indicating intact spermatogenesis and presence of spermatozoa. Germinal epithelial height was measured using the image analyzer software ImageJ. Observations were also documented with regard to histological appearance of Sertoli and Leydig cells as well as the basement membrane. The numerical data was analyzed with SPSS version 23. Results: Light microscopic study showed complete spermatogenesis in the testis of the animals in Control as well as Nigella Seeds group. Cisplatin treated animals suffered significant loss of spermatocytes, spermatids and spermatozoa. Statistically significant reduction (P <0.005) was observed for all the parameters (Mean Johnsen Score, Mean Germinal Epithelium Height, Mean weight loss and Mean Testicular Weight) when the Cisplatin-treated animals were compared to the other three experimental groups. These results signified that while Cisplatin treatment resulted in severe testicular toxicity, co-administration of an aqueous solution of Nigella seeds mitigated these changes to a statistically significant level. Conclusion: On the basis of the results of this study it was concluded that Nigella seeds in the form of an aqueous solution have an ameliorative effect against the testicular toxicity of Cisplatin.